Interview with Jack Keefe of Black Tickle - Memorial University of Newfoundland. Extension Service (Memorial University of Newfoundland. Extension Service, 1960)
An interview with Jack Keefe of Black Tickle about the fishery. Black and white. Lacks credits. Minor distortion throughout.